Cover Image. (18th July 2018) - Bayarkhangai, Buuvee; Noureldin, Suzan; Yu, Liting; Zhao, Na; Gu, Yaru; Xu, Hanmei; Guo, Changying
Abstract : The cover image, by Buuvee Bayarkhangai et al., is based on the Review A comprehensive and perspective view of oncoprotein SET in cancer, DOI: 10.1002/cam4.1526 .